2014
DOI: 10.1038/bjc.2013.832
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sunitinib in elderly patients with metastatic renal cell carcinoma

Abstract: Background:We retrospectively analyzed sunitinib outcome as a function of age in metastatic renal cell carcinoma (mRCC) patients.Methods:Data were pooled from 1059 patients in six trials. Kaplan–Meier estimates of progression-free survival (PFS) and overall survival (OS) were compared by log-rank test between patients aged <70 (n=857; 81%) and ⩾70 (n=202; 19%) years.Results:In first-line patients, median PFS was comparable in younger and older patients, 9.9 vs 11.0 months, respectively (HR, 0.89; 95% CI: 0.73–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 48 publications
5
51
1
1
Order By: Relevance
“…However, our study indicated that treatment with targeted therapy would likely lead to better clinical outcomes in elderly mRCC patients, consistent with findings reported by others 3134. Although safety and tolerability of targeted agents in elderly patients were not reviewed in our study, others have reported that they were generally similar to those in younger patients 31,3335. Therefore, although retrospective in nature, our study, as well as other available data, supports the clinical benefit of using targeted therapy in elderly mRCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, our study indicated that treatment with targeted therapy would likely lead to better clinical outcomes in elderly mRCC patients, consistent with findings reported by others 3134. Although safety and tolerability of targeted agents in elderly patients were not reviewed in our study, others have reported that they were generally similar to those in younger patients 31,3335. Therefore, although retrospective in nature, our study, as well as other available data, supports the clinical benefit of using targeted therapy in elderly mRCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…During our preparation for this study, another retrospective data analysis from six trials revealed a slightly better, but not significant, median PFS (11.0 vs 9.9 months) and median OS (25.6 vs 23.6 months) in older, as opposed to younger, mRCC patients receiving first-line sunitinib treatment. Adverse effects occurred more often in older than in younger patients 12. Likewise, our study found that older patients with advanced RCC and mRCC in the People’s Republic of China could benefit from targeted therapy, with even better clinical outcomes.…”
Section: Discussionsupporting
confidence: 64%
“…To the best of our knowledge, research focusing on response to targeted therapy among RCC patients of different ages is currently lacking. Hutson and colleagues have reported that median progression-free survival (PFS) and overall survival (OS) are comparable in younger and older (≥70 years) mRCC patients receiving sunitinib, suggesting that elderly patients may achieve additional clinical benefit 12. Similar results were found from the data of another group of patients treated with sorafenib 13.…”
Section: Introductionmentioning
confidence: 59%
“…This condition is not recapitulated in standard mouse experiments and we have previously characterized C57BL/6 ApoE-/-mouse strain as an informative, humanlike model of age-related vascular changes, which impact tumor progression (Klement, St, Milsom, May, Guo, Yu, Klement, and Rak 2007). Using this approach we interrogated the effects of sunitinib, an antiangiogenic agent given to patients with metastatic cancers, essentially irrespectively of their vascular ageing status (Vazquez, Leon, Fernandez, Lazaro, Grande, and Aparicio 2012;Escudier, Albiges, and Sonpavde 2013;Hutson et al 2014).…”
Section: Discussionmentioning
confidence: 99%